Forensic Support of Pre-Trial Investigative and Inquiry Agencies’ Activities on Combating Crime (Bulletin of Kharkiv National University of Internal Affairs, 2021)
The problematic issues of forensic support of the pre-trial investigation and inquiry agencies’ activities on counteracting criminal offenses on the territory of Ukraine have been studied. The elements have been characterized and the concept and essence of counteraction to crimes both from the theoretical point of view and from law enforcement activity have been defined. The author has analyzed national criminal procedural legislation, departmental normative and legal base and amendments to them concerning, in particular, introduction of a new position – the expert in criminalistics and the researched direction, as well as the genesis and further development of scientific points of view in regard to theoretical and applied issues of forensic support of the pre-trial investigation and inquiry agencies’ activities in the specified direction, as well as on improving the concept and essence of criminalistics as a science and its role in combating criminal offenses. The author has studied the issues of current state and tendencies of criminalistics development, existing problematic issues and expediency of changing the scientific paradigm of criminalistics, application of innovations, introduction of modern achievements in the field of telecommunication and digital technologies, communication lines, Internet and the ways of their practical usage and further improvement. It has been stated that today’s theoretical and applied problems of criminalistics are subject to careful study, it is necessary to introduce radical changes in general and in some areas, which requires its consolidation in the current legislation, with further reform of law enforcement agencies, expert institutions, prosecutor’s office and courts, as well as in law enforcement activity, which introduces modern advances of science and technology, including artificial intelligence and modern advances in chemistry, including molecular one, as well as physics, cybernetics, technologies for the manufacture of new metals, their alloys and innovation in other areas of knowledge. The author has argued the existence of such problematic issues as the improvement of forensic characteristics of certain types of crimes, forensic methodology that combines forensic techniques and tactics, contributes to the further improvement of methods of investigating certain types of crimes. The issues of further dissemination and application in law enforcement and expert activities of molecular genetical examinations promising for pre-trial investigation, in particular methods of DNA analysis, have been separately and widely studied. According to the results of the research, the author has provided specific propositions and recommendations on the researched direction of activity in the whole and its separate branches.
Keywords: criminalistics; genesis; scientific point of view; improvement; an investigator; an interrogator; a prosecutor; provision; counteraction to crime; science; forms; methods; methodology; scientific and technical means.